Art for art’s sake: Oscar Wilde’s Trajectory in Victorian Literature - Sulistya Ningtyas, S.S., M.A.; Retno Wulandari; Mytha Candria (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
The production of a literary work is influenced by the elements present in its literary field. Oscar Wilde, one of the classic authors of English literature, was significantly shaped by the literary field of the Victorian Era throughout his career. This study aims to explain the reconversion strategies Wilde employed to attain legitimacy as an English literary figure. Using Pierre Bourdieu’s theoretical framework and sociological approach to literature, the research traces Wilde’s accumulation of capital, strategies, and trajectory. From his background, Wilde possessed economic, cultural, social, and symbolic capital—assets that empowered him to hold a significant role within the literary field. However, the scandal surrounding his homosexuality severely damaged his reputation at the time. Ironically, this downfall led Wilde to publish a phenomenal work that explored the concept of duality. With the widespread influence of the principle of “art for art’s sake” through the aestheticism movement, the public began to view art as something that should be appreciated purely for its beauty. This reconversion of capital ultimately enabled Wilde to gain legitimacy within the English literary field of the Victorian Era.